2021
DOI: 10.21203/rs.3.rs-139951/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Placental Mesenchymal Stem Cells Ameliorate Liver Fibrosis in Mice by Upregulation of Caveolin1 in Hepatic Stellate Cells

Abstract: Background: Liver fibrosis (LF) is a common pathological process characterized by the activation of hepatic stellate cells (HSCs) and accumulation of extracellular matrix. Severe LF causes cirrhosis and even liver failure, a major cause of morbidity and mortality worldwide. Transplantation of human placental mesenchymal stem cells (hPMSCs) has been considered as an alternative therapy, replacing liver transplantation in clinical trials, to treat LF. However, the underlying mechanisms and the appropriate time w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Additionally, if substantial inflammation is confirmed, physicians should initially attempt anti-inflammatory therapy, which might decrease bowel wall edema and thickness, with subsequent relief of the obstructive symptom [26]. Our previous studies have also shown that the anti-inflammatory effect of MSCs is very important in the treatment of liver fibrosis [27]. The above experiments indicated that primed hADSCs of IDO-1 expression increased had significant anti-inflammatory and antifibrotic effects than untreated hADSCs.…”
Section: Hadscs Ameliorated Tnbs-induced Colitis Through An Ido-1-dep...mentioning
confidence: 88%
“…Additionally, if substantial inflammation is confirmed, physicians should initially attempt anti-inflammatory therapy, which might decrease bowel wall edema and thickness, with subsequent relief of the obstructive symptom [26]. Our previous studies have also shown that the anti-inflammatory effect of MSCs is very important in the treatment of liver fibrosis [27]. The above experiments indicated that primed hADSCs of IDO-1 expression increased had significant anti-inflammatory and antifibrotic effects than untreated hADSCs.…”
Section: Hadscs Ameliorated Tnbs-induced Colitis Through An Ido-1-dep...mentioning
confidence: 88%
“…TGR5 up-regulation participates in human placental mesenchymal stem cell transplantation-relieved primary sclerosing cholangitis. 123 TGR5 KO or inhibition leads to more abundant pro-inflammatory subtype of macrophages and suppressed tumour progression in NSCLC 65 ; TGR5 activation ameliorates motor deficits and cognitive impairment in a subchronic Parkinson's disease mouse model 124 ; and DCA induces gastric intestinal metaplasia by activating TGR5/STAT3/KLF5 axis. 125 Tgr5 KO mice show greater steatosis and inflammation by increasing liver macrophages recruitment 59 ; Tgr5 KO mice show decreased hair area and length, skin thickness, and the ratio of anagen and telogen, collagen, and mast cell number and loss the bone mass than WT group.…”
Section: Years Potential Effectmentioning
confidence: 99%
“…FGF21 inhibits further activation of HSCs by suppressing the TGF-β/Smad3C signaling pathway, thereby stopping the progression of LF. Furthermore, it has been found that upregulation of Cav1 inhibits the TGF-β/Smad signaling pathway, mainly by decreasing the phosphorylation of Smad2, thereby inhibiting activated HSCs [26] . High mobility group box 1 protein (HMGB1) and toll-like receptor 4 (TLR4) are key mediators of the pro-inflammatory response.…”
Section: Role Of Cytokines and Smad Signaling Pathwaymentioning
confidence: 99%